2018
DOI: 10.1016/j.neurobiolaging.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ADAM10 by miR-140-5p and potential relevance for Alzheimer's disease

Abstract: Recent reports in Alzheimer's disease (AD) research suggest that alterations in microRNA (miRNA) expression are associated with disease pathology. Our previous studies suggest that A Disintegrin and Metalloproteinase 10 (ADAM10) expression is important in AD and could be modulated by an extended regulatory region that includes the 3' untranslated region. In this study, we have investigated the role of trans-acting factors in ADAM10 gene regulation. Our study shows that miRNA-140-5p has enhanced expression in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…MicroRNA (miRNA) is a single-stranded non-coding RNA, which can be used as potential drug targets to treat human diseases [12] , [13] , [14] , [15] . Previous studies showed that miR-140-5p has the biological activities including regulating adipocyte differentiation, inhibiting cancer growth and modulating Alzheimer's disease [16] , [17] , [18] . Furthermore, our previous work has also proved that miR-140-5p plays an important role in DOX- induced cardiotoxicity by inducing myocardial oxidative stress via targeting nuclear erythroid factor 2-related factor 2 (Nrf2) and silent information regulator factor 2-related enzyme 2 (Sirt2) [19] .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNA (miRNA) is a single-stranded non-coding RNA, which can be used as potential drug targets to treat human diseases [12] , [13] , [14] , [15] . Previous studies showed that miR-140-5p has the biological activities including regulating adipocyte differentiation, inhibiting cancer growth and modulating Alzheimer's disease [16] , [17] , [18] . Furthermore, our previous work has also proved that miR-140-5p plays an important role in DOX- induced cardiotoxicity by inducing myocardial oxidative stress via targeting nuclear erythroid factor 2-related factor 2 (Nrf2) and silent information regulator factor 2-related enzyme 2 (Sirt2) [19] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the ischemic stroke, many other diseases also exhibited dysregulated expression of miR-140-5p, such as hepatocellular carcinoma, colorectal cancer, and pulmonary arterial hypertension [28][29][30]. Previous reports also discovered various biological activities of miR-140-5p, including adipocyte differentiation regulation, cancer growth inhibition, as well as Alzheimer's disease modulation [31][32][33]. It is generally known that neuron protection is an important therapeutic target in ischemic stroke [34].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the contributions of miRNAs to AD development and progression have also been demonstrated to largely rely on their ability to alter the expression of toxic protein‐coding genes. For instance, miR‐140‐5p expression is enhanced in the AD postmortem brain hippocampus, and it downregulates ADAM10 that poses neuroprotective effect in early AD . The expression of miR‐29 is decreased in AD patients who have high levels of human β‐secretase, and employment of miR‐29 suppresses human β‐secretase‐induced Aβ peptide .…”
Section: Discussionmentioning
confidence: 99%